2019
DOI: 10.1182/blood-2019-126075
|View full text |Cite
|
Sign up to set email alerts
|

Potency Equated Porcine and Bovine Mucosal Heparin Are Bioequivalent in Terms of Biochemical and Pharmacological Effects

Abstract: Introduction: Currently, there is a shortage of porcine heparin due to limited availability of porcine mucosa and supply chain issues. Bovine heparin has been used for clinical purposes globally and is being considered for reintroduction in the U.S. On a mass basis, commercially available porcine heparins exhibit a higher potency (180-220 units/mg) than their bovine counterpart (130-150 units/mg). Therefore, at gravimetric levels, the porcine heparins exhibit stronger biochemical and pharmacological effects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therefore, the anticoagulant activity of porcine and bovine heparin, when used at adjusted anti-Xa unit levels, is comparable. 26 Baig et al 27 reported that the use of bovine heparin in patients under dialysis in place of porcine heparin, and that the lower anti-Xa activity of the bovine heparin did not significantly affect the patients or the operation of the dialyzer. This indicates that the use of bovine heparin in dialysis, regardless of its lower potency compared to porcine, does not impact the efficacy and safety of the patients.…”
Section: Bovine Heparinmentioning
confidence: 99%
“…Therefore, the anticoagulant activity of porcine and bovine heparin, when used at adjusted anti-Xa unit levels, is comparable. 26 Baig et al 27 reported that the use of bovine heparin in patients under dialysis in place of porcine heparin, and that the lower anti-Xa activity of the bovine heparin did not significantly affect the patients or the operation of the dialyzer. This indicates that the use of bovine heparin in dialysis, regardless of its lower potency compared to porcine, does not impact the efficacy and safety of the patients.…”
Section: Bovine Heparinmentioning
confidence: 99%